THE CONTEXTUAL INTERPRETATION OF POLYGAMY VERSES IN THE QUR'AN - Syarif, Fajar (Journal of Islamic Studies and Humanities, 2020)
This study concluded that polygamy practiced by some Muslims did not have adequate syar'i arguments and were not in accordance with the principles of social justice outlined in the Qur'an. Whereas the arguments that have been used by classical scholars only constitute the justification of the verses of the Qur'an to synchronize classical culture with gender bias. The verses of polygamy in essence contain the rules of justice in treating orphans and not for the legality of polygamy in Islam.